Multiple endocrine neoplasia 1: a broad overview - Rachel Thompson; Christine S. Landry (SAGE Publishing, 2021)
This review article discusses the diagnoses and treatment of patients with multiple endocrine neoplasia type 1 (MEN 1). The most common tumors associated with MEN 1 are located in the pancreas, pituitary, and parathyroid glands. Less common tumors include neuroendocrine tumors of the lung and thymus, adrenal tumors, and cutaneous lesions. This article describes the diagnosis, clinical manifestations, treatment, and surveillance of tumors associated with patients who are diagnosed with MEN 1.